ADP-Induced Platelet Release Reaction in Acute Stroke - Mulley, G P; Heptinstall, S; Taylor, P M; Mitchell, J R A (Thrombosis and Haemostasis, 1983)
The extent of the ADP-induced platelet release reaction has been determined in 107 patients admitted to hospital with acute stroke. In 43 of the patients a precise diagnosis was obtained and in those with proven thromboembolic stroke the mean extent of the release reaction was significantly higher than for those with either primary haemorrhagic stroke or those with subarachnoid haemorrhage. Enhanced platelet reactivity was also found in the patients in whom a precise diagnosis could not be obtained, most of whom probably had cerebral infarction. Comparison of the results obtained for patients with stroke with those obtained for individuals who had not experienced a stroke showed that thromboembolic stroke is associated with platelet hyperactivity while haemorrhagic stroke is associated with platelet hypoactivity. The part that abnormalities of platelet behaviour, whether causal or consequential, might play in occlusive stroke and intra-cranial haemorrhage is discussed and the need for large scale prospective studies is emphasised.
Keywords: Blood platelets; Thromboembolic stroke; Primary haemorrhagic stroke; Subarachnoid haemorrhage